Put up the firewalls. (Economist, 2015)
The article focuses on a June 4, 2015 report by the U.S. Office of Personnel Management that revealed around four million personal records of current and former federal employees had been hacked, possibly by a group connected to the Chinese government. It states the information might include job assignments, training information, performance ratings, and Social Security numbers. It comments on the vulnerability of U.S. government records due to the failure to use common authentication systems.